A case of cardiac sarcoidosis presenting with double tachycardia - Takahashi, Keiko (J Arrhythm, 2015)
Although the most feared cardiac manifestation in cardiac sarcoidosis is the onset of ventricular arrhythmia, some patients may present with supraventricular arrhythmias. We present a rare case of cardiac sarcoidosis associated with double tachycardia manifesting as atrial flutter and ventricular tachycardia.